Foreign policy as a means of the AKP's struggle with Kemalism in relation to domestic variables - EGE, ASLI (My University, 2022)
This article provides analyzes how foreign policy affects domestic politics, in particular the AKP\"s struggle with Kemalism. It examines how Kemalism was delegitimized through the initial democratic, pro-European Union and pro-West discourse of the AKP. It then analyzes Kemalism\"s marginalization under the civilizational, neo-Ottoman discourse advanced by Ahmet Davutoglu. Finally, it explores Kemalism\"s alienation through the opposition CHP, which has been impacted by the neo-Ottoman discourse, as currently constructed. It concludes that the AKP\"s struggle with Kemalism did not end even when it established control over the state and when the ideological Kemalist nation-state identity was replaced by a new content in the form of an Ottoman-Islamic civilization. The article relies on a method of interpretative analysis of the AKP and Kemalist movements.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Social Sciences and Humanities; Sociology; ALAN ÇALIŞMALARI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); AREA STUDIES; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; General Social Sciences; Social Sciences & Humanities; AKP; kemalism; Turkish foreign policy; neo-Ottomanism; democratization; islamization; TURKEYS; DEMOCRATIZATION; WESTERN; PARTY; RULE